Cross-Cultural Communication: Communication Accommodation Experiences of Pattani Students with Javanese Students at IAIN Tulungagung - Dwi Astuti Wahyu Nurhayati; Mohamad Jazeri (Yayasan Visi Intan Permata, 2019)
Cultural differences between native and Indonesian culture makes foreign students in Indonesia experience a culture shock. Such case occurs on students from Pattani, South Thailand, who study in IAIN Tulungagung. To overcome that culture shock, Pattani students do communication accommodation to make them feel comfortable in a new environment, and thus can be accepted by Javanese students from Indonesia. This research was a kind of qualitative study. The data were collected by using observation and interview techniques. To find out the forms of communication accommodation performed by Pattani students, the researchers adopted communication accommodation theory by Giles. The results of this research revealed that there were two forms of communication accommodation performed by Pattani student. Firstly, convergence, was performed when Pattani students tried to level communication behavior with their speech partners. Convergence done by Pattani students can be classified into pre-convergence, convergence process, and post convergence. Secondly, divergence, is defending Pattani identity when communicating with Javanese students. Divergence accommodation were performed in two forms namely verbal and non-verbal.